Palladium-catalyzed hydroboration reaction of unactivated alkynes with bis (pinacolato) diboron in water. Issue 16 (29th March 2022) - Yang, Ming; Yu, Yunzi; Ma, Wenxia; Feng, Yuqin; Zhang, Gang; Wu, Yaqi; Zhou, Fanyu; Yang, Yongsheng; Liu, Dezheng
Abstract : A highly efficient and mild palladium-catalyzed hydroboration of unactivated internal alkynes in water. Abstract : A highly efficient and mild palladium-catalyzed hydroboration of unactivated internal alkynes in water is described. Both aryl- and alkyl-substituted alkynes proceeded smoothly within the reaction time to afford the desired vinylboronates in moderate to high yields. Bis (pinacolato) diboron was used to afford α- and β-hydroborated products in the presence of HOAc. These reactions showed high reactivities and tolerance, thus providing a promising method for the synthesis of alkenyl boron compounds.